Large‐Scale Fracture Systems Are Permeable Pathways for Fault Activation During Hydraulic Fracturing. Issue 3 (11th March 2021) - Igonin, Nadine; Verdon, James P.; Kendall, J.‐Michael; Eaton, David W.
Abstract: Induced seismicity due to fluid injection, including hydraulic fracturing, is an increasingly common phenomenon worldwide; yet, the mechanisms by which hydraulic fracturing causes fault activation remain unclear. Here we show that preexisting fracture networks are instrumental in transferring fluid pressures to larger faults on which dynamic rupture occurs. Studies of hydraulic fracturing‐induced seismicity in North America have often used observations from regional seismograph networks at distances of 10s of km, and as such lack the resolution to answer some of the key questions about triggering mechanisms. To carry out a more detailed analysis of the mechanisms of fault activation, we use data from a dense sensor array located at a hydraulic‐fracturing site in Alberta, Canada. The spatiotemporal distribution of event hypocenters, coupled with measurements of seismic anisotropy, reveal the presence of preexisting fracture corridors that allowed communication of fluid‐pressure perturbations to larger faults, over distances of 1 km or more. The presence of preexisting permeable fracture networks can significantly increase the volume of rock affected by the pore‐pressure increase, thereby increasing the probability of induced seismicity. This study demonstrates the importance of understanding the connectivity of preexisting natural fractures for assessing potential seismic hazards associated with hydraulic fracturing of shale formations and offers a detailed case exposition of induced seismicity due to hydraulic fracturing. Plain Language Summary: Felt earthquakes have been observed in North America, Asia and the U.K. during, or shortly after, hydraulic fracturing for shale gas development. An increase in fluid‐pressure is widely regarded as the primary mechanism for fault activation, but current models do not adequately explain time delays (hours‐to‐days) and activation distance (up to 1 km) from the injection well. Using high‐resolution data acquired in close proximity to hydraulic‐fracturing operations, we show that preexisting natural fracture systems can provide permeable conduits for diffusion of fluid pressure to a fault that is of sufficient size to host a felt earthquake. Our model explains both the observed time delay and activation distance and demonstrates that the mapping of fracture networks is an important consideration in risk analysis for induced seismicity. Key Points: Dense array monitoring shows delay times (hours‐to‐days) and offset activation distances (up to a km) from injection time There are highly permeable fracture networks within the reservoir, based on b‐values, event timing, MTI and anisotropy analysis Pore pressure perturbation along existing fracture networks resulted in fault activation at a distance